1998
DOI: 10.1002/(sici)1097-0215(19980504)76:3<312::aid-ijc4>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Retention of theCDKN2A locus and low frequency of point mutations in primary and metastasic cutaneous malignant melanoma

Abstract: CDKN2A has been found mutated in melanoma families which show linkage to chromosome 9p21. In contrast, a low mutation rate has been found in melanomas, suggesting that CDKN2A might not be the first target for mutation in the development of this type of tumour. To elucidate the role of the CDKN2A gene and its alternative transcript p19ARF in the development of cutaneous malignant melanoma (CMM) we have analyzed 48 primary and metastasic CMM tumours for mutations and for loss of heterozygosity (LOH). Only one po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Marshall et al (1997) mapped a deleted region in neuroblastoma centromeric of the p16 INK4A gene. Both Puig et al (1995) and Ruiz et al (1998) reported chromosome 9p deletions in cutaneous malignant melanoma outside of the p16 INK4A gene. Wiest et al (1997) mapped a region of homozygous deletion on chromosome 9p in squamous cell carcinoma of the lung proximal to the p16 INK4A locus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marshall et al (1997) mapped a deleted region in neuroblastoma centromeric of the p16 INK4A gene. Both Puig et al (1995) and Ruiz et al (1998) reported chromosome 9p deletions in cutaneous malignant melanoma outside of the p16 INK4A gene. Wiest et al (1997) mapped a region of homozygous deletion on chromosome 9p in squamous cell carcinoma of the lung proximal to the p16 INK4A locus.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of primary tumors, however, has shown that not all 9p21 deletions encompass these three tumor suppressor genes. Chromosome 9p deletions outside of the p16 INK4A /p14 ARF and p15 INK4B region have been described in gliomas (Farrell et al, 1997;Marshall et al, 1997), pituitary adenomas (Farrell et al, 1997), lung cancers (Kim et al, 1997;Schmid et al, 1998;Wiest et al, 1997), melanomas (Flores et al, 1996;Ruiz et al, 1998), bladder cancers (Habuchi et al, 1995;Keen and Knowles, 1994), and breast cancers . Hence, it is important to determine if there are other expressed genes on chromosome 9p21 that may be deleted in malignant cells.…”
Section: Introductionmentioning
confidence: 99%
“…Linkage analysis in melanoma prone families (Ruiz et al, 1999) and loss of heterozygosity studies in melanoma tumours (Puig et al, 2000;Ruiz et al, 1998) also suggest the existence of other melanoma genes located in 9p21. The role of p14ARF in melanoma susceptibility remains controversial and has been dicult to resolve because of its unusual genomic structure; p14ARF shares signi®cant coding sequence with p16…”
Section: Ink4bmentioning
confidence: 99%
“…This is consistent with previous studies which have shown that deletion at CDKN2A appears to be the major mechanism of CDKN2A inactivation in primary melanomas (Funk et al,1998; Fujimoto et al,1999; Rizos et al,1999; Cachia et al,2000; Straume et al,2002; Zhang and Rosdahl,2004). We did not screen for mutations as previous studies have consistently shown small sequence alterations to be uncommon (Ruiz et al,1998; Cachia et al,2000). Epigenetic silencing of CDKN2A by methylation (Gonzalgo et al,1997; von Eggeling et al,1999; Straume et al,2002) could not be investigated in this study due to constraints on DNA availability from small tumors.…”
Section: Discussionmentioning
confidence: 99%